Glocal approach for Asian brands - Sheikh Ahmad, Fauziah (2007)
Annual Digital Marketing Conference connects digital marketing professionals in Canada with new customers, ideas, technologies, and business opportunities. Learn to attract and satisfy customers through digital strategies, social media marketing, search engine marketing, content marketing, analytics, mobile integration, and other best practices.